Caribbean Integration—Lessons for the Pacific?. Issue 1 (28th December 2014) - Warner, Robert; Anatol, Marlon
Abstract: The members of the Pacific Islands Forum have recently considered a quite critical review of the Pacific Plan for strengthening regional cooperation and integration. The Caribbean Community (CARICOM), another grouping encompassing a number of small island developing states, has also been contemplating highly critical assessments of the nature of its approach to regionalism, and of the institutions that have been put in place to give effect to this approach. Are there lessons for the Pacific from the Caribbean experience? This article looks at aspects of the approaches to regionalism and economic integration adopted in the Caribbean, and considers parallels with the situation in the Pacific. It suggests that the CARICOM experience puts into question elements of the logic and overall approach to integration being pursued in both regions (and being urged by external partners).